Advances in the structures, mechanisms and targeting of molecular chaperones - Jinying Gu; Yanyi He; Chenxi He; Qiuyue Zhang; Qifei Huang; Shangjun Bai; Ruoning Wang; Qidong You; Lei Wang (Signal Transduction and Targeted Therapy)
Abstract Molecular chaperones, a class of complex client regulatory systems, play significant roles in the prevention of protein misfolding and abnormal aggregation, the modulation of protein homeostasis, and the protection of cells from damage under constantly changing environmental conditions. As the understanding of the biological mechanisms of molecular chaperones has increased, their link with the occurrence and progression of disease has suggested that these proteins are promising targets for therapeutic intervention, drawing intensive interest. Here, we review recent advances in determining the structures of molecular chaperones and heat shock protein 90 (HSP90) chaperone system complexes. We also describe the features of molecular chaperones and shed light on the complicated regulatory mechanism that operates through interactions with various co-chaperones in molecular chaperone cycles. In addition, how molecular chaperones affect diseases by regulating pathogenic proteins has been thoroughly analyzed. Furthermore, we focus on molecular chaperones to systematically discuss recent clinical advances and various drug design strategies in the preclinical stage. Recent studies have identified a variety of novel regulatory strategies targeting molecular chaperone systems with compounds that act through different mechanisms from those of traditional inhibitors. Therefore, as more novel design strategies are developed, targeting molecular chaperones will significantly contribute to the discovery of new potential drugs.